EXPERIENCES OF PREGNANT WOMEN AT THE PROCESS OF LABOR: SCOPING REVIEW - Ria Harnita Sari; Farida Kartini; Menik Sridaryanti (Universitas 'Aisyiyah Yogyakarta, 2021)
Background: Each pregnant woman desires normal labor and the trust from health staffs and the support from other people. This literature review is to determine the experiences of pregnant women at labor process. Aim: Knowing the psychological and support of pregnant women. Methods: Five stages were used to conduct a scoping review. The stages include identifying research questions, identifying relevant studies, selecting studies, charting data and compiling, summarizing and reporting the results. Result: the experience of giving birth in pregnant women includes experiences related to the knowledge and information received by them, adjustment, fears, hopes, readiness for childbirth, support from family and husbands. The information given can become the answer on the question and assist women in managing their mind, better understanding, and the support from other people. Conclucion: Interestingly, it was found that the women wanted a normal delivery and the trust of a health worker (midwife) where they also needed empowerment and support from others.